Reproduction biotechnologies in germplasm banking of livestock species: a review. Issue 5 (24th August 2017) - Morrell, J.M.; Mayer, I.
Summary: Many biotechnologies are currently used in livestock breeding with the aim of improving reproductive efficiency and increasing the rate of genetic progress in production animals. Semen cryopreservation is the most widely used cryobiotechnology, although vitrification techniques now allow embryos and oocytes to be banked in ever-increasing numbers. Cryopreservation of other types of germplasm (reproductive tissue in general) is also possible, although the techniques are still in the early stages of development for use in livestock species. Although still in their infancy, these techniques are increasingly being used in aquaculture. Germplasm conservation enables reproductive tissues from both animals and fish to be preserved to generate offspring in the future without having to maintain large numbers of living populations of these species. However, such measures need careful planning and coordination. This review explains why the preservation of genetic diversity is needed for livestock and fish, and describes some of the issues involved in germplasm banking. Furthermore, some recent developments in semen handling leading to improved semen cryopreservation and biosecurity measures are also discussed.